Numerical Investigation of Unsteady Rotor–Stator Interaction Mechanism and Wake Transportation Characteristics in a Compressor with Non-Uniform Tip Clearance Rotor - Guochen Zhang; Zhipeng Li; Qijiao Wang; Zhihui Xu; Zhiyuan Cao (Energies, 2023)
This study aims to numerically investigate a transonic compressor by solving the unsteady Reynolds-averaged Navier–Stokes equations. The flow mechanisms related to unsteady flow were carefully examined and compared between rotors with non-uniform tip clearance (D1) and small-value tip clearance (P1). The unsteady flow field near the 50% and 95% blade span characterized by unsteady rotor–stator interaction was analyzed in detail for near-stall (NS) conditions. According to the findings, the perturbation of unsteady aerodynamic force for the stator is much bigger than that of the rotor. At the mid-gap between the rotor and stator, the perturbation of tangential velocity of the D1 scheme in the rotor and stator frame is reduced. At the rotor’s outlet region, the perturbation intensity is divided into three main perturbation regions, which are respectively concentrated in the TLV near the upper endwall, the corner separation at the blade root, and the wake of the whole blade span. Through the analysis of the wake transportation characteristics, it was found that when the wake passes through the stator blade surface, the wake exerts a substantial influence on the flow within the stator passage. It further leads to notable pressure perturbations on the stator’s surface, as well as affecting the development and flow loss of the boundary layer. The negative jet effect induces opposite secondary flow velocity on both sides of the wake near the stator’s surfaces. Therefore, the velocity at a specific point on the stator’s suction surface will decrease and then increase. Conversely, the velocity at a particular point on the pressure surface will increase and then decrease.